(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article describes the stage of the banking system being updated under the name of Bank 5.0 and the processes involved in it. Therefore, the article aims to emphasize on the issues of solving the problems that have arisen in the banking system in the period after the global pandemic. The article shows the essence of the subject, including several approaches in the stage of Banking 5.0.